Onde estão as rosas? As mulheres no movimento agroecológico brasileiro e o feminismo decolonial - Marina Fernandes Bispo de Siqueira; Thiago William Pereira Barcelos; Gabriel Antonio Silveira Mantelli (Les Cahiers ALHIM)
This article explores the relationship between the agroecological movements of women in the Brazilian context and the contributions of Latin American decolonial feminism. We mobilize the centrality of gender to take into account the epistemic strength of local histories and to think the theory through the political praxis of subaltern groups. We highlight the need to analyze how these movements interpret feminism. In methodological terms, the article is built from a critical view of social relations and the mobilization of law. We use the history of women inserted in the movements mentioned above and how they relate (or can relate) directly to the theoretical contributions of the Latin American decolonial movement. Our research indicates that there is a dialogue of knowledge in the field of agroecological struggles and mobilized by women, whose objective is the resistance against coloniality, not always understood in these terms, and the consolidation of local knowledge.